GAMBARAN DUKUNGAN KELUARGA PADA LANSIA DENGAN STROKE DI UPTD KESMAS SUKAWATI I GIANYAR - Pranoto, A.H; Yudhawati Yudhawati; Ni Luh Putu .S (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2020)
Background: Stroke is a cardiovascular disease that is most commonly found in society, especially in Indonesia. Stroke sufferers need support from people around them, especially family, who are needed to serve sufferers so they don't lead to depression. Family support consists of information support, service support, instrumental support and emotional support so that it is hoped that the family can help the patient's needs so that the patient can lead to an independent direction. Method: This scientific paper uses a descriptive method with a quantitative approach using a measuring instrument in the form of a questionnaire. The population in this study was the elderly with stroke in the working area of ??the UPTD Kesmas I Gianyar with 36 samples. The sampling technique used in this study was purposive sampling. Results: 10 respondents or 27.8% had good family support, 14 respondents or 38.9% had sufficient family support and finally 12 respondents or 33.3% had less family support. Conclusion: Most of the respondents received family support in the adequate range and were asked to provide greater support to improve the quality of life of the elderly. It is hoped that further researchers will be able to develop research related to family support elderly people with stroke at the UPTD Kesmas Sukawati I districts Gianyar